Peran Bumdes Maria Maju Untuk Mewujudkan Kemandirian Ekonomi (Studi Kasus Desa Maria Kecamatan Wawo Kabupaten Bima) - Hawa, Siti; Sokarina, Ayudia; Suryantara, Adhitya Bayu (Lembaga Riset Ilmiah, 2022)
The purpose of this study was to determine the role of BUMDes Maria Maju to realize economic independence in Maria Village, Wawo District, Bima Regency. The research method used is a qualitative method with descriptive analysis. Data collection techniques used are interviews, observation, and documentation. The results of this study indicate that the role of BUMDes in supporting village economic independence consists of: BUMDes service aspects which have implications for village economic independence, accountability aspects have implications for increasing village original income, aspects of improving living standards have implications for rural economic growth and equity, and regulatory compliance aspects. legislation has implications for the ability to manage village potentia